O que é que a Adivinhação Adivinha? - Paulo Granjo (Cadernos de Estudos Africanos)
Although it is often assumed that the predominant southern African systems of misfortune interpretation are deterministic, the notion of “deterministic chaos” seems to be more accurate to understand the underlying principles of the Mozambican divination with tinhlolo. This divination practice does not foresee the future but both the past causes to the present situation, and how would be the future (assumed as mutable and dynamic) if the current conditions would remain unchanged. The aim is, however, to manipulate effectively such conditions, in order to achieve the most desirable result. This system is based on a deterministic structure, it seeks to explain and to regulate uncertainty, but its outcome is chaotic due to the complexity of the involved factors, unknowable in their totality and characterized by agency. To understand it as a “domestication of uncertainty” system legitimates new comparison fields worldwide (including with the probabilistic notion of “risk”), and refocus the study of Ngoma-like phenomena, from their reproduction mechanisms as “affliction cults” to their underlying logics and world views.